Trends in species richness and density of Teucrium polium L. (Lamiaceae) over time and space - Alrawashdeh, I. M.; Alrawashdeh, N. Q.; Amri, A. (Penerbit Universiti Kebangsaan Malaysia, 2015)
The aim of this study was to investigate the species diversity and species richness of vegetation cover with a focus on Teucrium polium L. species. Density and other diversity parameters were used to assess the impact effect of climate change at four sites within Al-Sult area of Jordan over 2010 to 2012 period. A total of 179 quadrates of 1m² each were used to survey the species richness and density and to estimate the Shannon diversity index based on the nature of vegetation. The rainfall recorded by the Agricultural Department-Statistics section was used to characterize the climatic conditions. The results of diversity among studied sites showed higher species richness and density in the West sites compared to the rest of the sites. Shannon diversity index was highest at Southern site (19.3) and showed a decrease from 2010 to 2012 which could be explained by the trend in rainfall.